Effectiveness of irrigation with chlorhexidine after removal of mandibular third molars: a randomised controlled trial. Issue 1 (January 2018) - Cho, H.; David, M.C.; Lynham, A.J.; Hsu, E.
Abstract: To evaluate the effect of postoperative irrigation with chlorhexidine on inflammatory complications after the extraction of lower third molars under local anaesthesia, we recruited 100 patients to participate in a controlled, single-blind, randomised clinical trial. They were assigned to one of two groups: the intervention group (postoperative irrigation of the surgical site with chlorhexidine for seven days) or the control group (postoperative chlorhexidine mouth rinse for seven days). The primary outcome variables were pain, swelling, trismus, infection, and alveolar osteitis. The secondary outcome variables were wound dehiscence and food impaction. A total of 95 participants completed the study (47 in the irrigation group and 48 in the rinse group). In the irrigation group, alveolar osteitis and facial swelling had reduced significantly at seven days postoperatively (both p < 0.01). Pain scores had also reduced significantly at seven days (p < 0.01), but not at 48 hours, and patients had lower levels of food impaction (p < 0.01) and less severe symptoms (p = 0.02). Routine irrigation with chlorhexidine after the extraction of third molars helps to reduce pain and lowers the incidence of alveolar osteitis.